Konsep Pengembangan Kawasan Krueng Aceh Melalui Perancangan Waterfront Mall dengan Penerapan Prinsip-Prinsip Arsitektur Tepi Air - Siti Zahrina Fakhrana (Jurnal Ilmiah Mahasiswa Arsitektur dan Perencanaan, 2017)
The development of Banda Aceh City influences the people’s lifestyles. It’s indicated by the people are becoming more consumptive. Therefore, it’s important to provide facilities not only for fulfilling the lifestyle, but also as a place for people to kill their boring urban life by providing several beauty natural places. Waterfront mall is expected to be a facility fulfillment for urban lifestyles, shopping center as well as providing entertainment which has recreational waterfront architectures by utilizing the beauty of Krueng Aceh’s waterfront area. Ultimately, it will increase an image of  waterfront area, and become the supporting facility for community public space.